4 - Residents’ Perceptions of Property Rating in a Traditional African City - Afon, Abel (Africa Development, 2021)
The success of any revenue generation drive by government depends on the support shown by an area’s residents. This in turn depends on the latter’s perceptions of the revenue. This study examines the influence of residents’ perceptions of a property tax in the different residential districts of Ogbomoso, Oyo State, Nigeria. Two of the ten political wards representing the three identifiable residential districts in the city were sampled. Two hundred and thirty-one occupants of dwellings were sampled, using the systematic random technique. The study identified that although variations exist in the socio- economic status of residents in the different residential districts, there was not much significant difference in the perceptions held of the tax. While residents’ level of awareness of the existence of the tax and the proportion of residents that had once paid the tax increased from the core residential area to the suburban, an inverse proportion of residents supported the justification for its imposition. The study concluded that the tax should be portrayed as charges on services provided and that the residents’ present negative perceptions of the tax would change if services are provided to meet minimal residents’ satisfaction.